ホッキョクケン コウクウキ カンソク (AAMP98)ノ ガイヨウ - 塩原, 匡貴; シオバラ, マサタカ; 藤井, 理行; フジイ, ヨシユキ; Shiobara, Masataka; Fujii, Yoshiyuki (2002)
P(論文) 北極圏の春季の大気中における微量気体およびエアロゾルの輸送，交換およびその化学過程を調べ，地球規模変化における極域の役割を理解するために，北極閤航空機観測計画（AAMP）を立案した．本計画では北樹域の対流圏および下部成層圏での観測を可能にするためにガルフストリ ームII型双発ジェット機（G-II）を使用した． このG-IIには二酸化炭素およびオゾンの連続測定装置，気体およびエアロゾルの採取装置，光学式エアロゾル粒子計数装置，PMS社の1次元および2次元粒子計測プロープ等が搭載された. 1998年3月上旬，日本からアラスカおよび北極点上空を経てスバールバル諸島に至るルートおよびその逆ルートにおいて大気観測を行った． 長距離飛行時の飛行高度は約12 kmだった．スバールバル諸島スピッツベルゲン島近海上空およびアラスカ州バ口 一上空では微景気体およびエアロゾルの濃度の鉛直プロファイル観測を行った． ノルウェー海上空ではポーラー・ローに伴う対流性雲システムの観測を行った．また，別種の雲観測としてスピッツベルゲン島近海の開水面上にできた境界層雲を観測した． The Arctic Airborne Measurement Program (AAMP) was planned to investigate the transport, exchange and chemical processes of gas and aerosol in the Arctic atmosphere in early spring, and further to understand their roles in global change. An instrumented aircraft, a Gulfstream II (G-11) twin-jet plane, was used for airborne measurements in the troposphere and lower stratosphere of the Arctic. For the AAMP 1998 campaign, the G-II was equipped with CO2 and O3 concentration measurement systems, gas and aerosol sampling systems, aerosol particle counters, and the PMS 1D and 2D airborne particle probes. The aircraft was flown from Japan to Svalbard via Alaska, passing over the North Pole, and on the reverse route, in the first half of March 1998. The approximate cruising altitude was 12 km for long-range flights. Vertical profiles of gas and aerosol concentrations were observed over Spitsbergen, Svalbard and Barrow, Alaska. A convective cloud system associated with a polar low was observed over the Norwegian Sea. Another cloud observation was made for marine boundary layer clouds over the open sea off Spitsbergen. departmental bulletin paper